MSH-coated WS2-C nano lubricating additive as well as preparation method and application thereof
By coating WS2 on the surface of magnesium silicate (MSH) and carbonized to form MSH@WS2-C nanocomposites, the problem of the reduction of friction performance of existing nanolubricating additives under long-term friction and wear is solved, and higher lubricating performance and wear resistance are achieved.
Patent Information
- Application Number
- CN202411892515.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
AI Technical Summary
In the case of long-term friction and wear of existing nanolubricating additives, the friction film is difficult to repair, resulting in a gradual decrease in friction performance and it is difficult to take into account time stability, dispersion stability in oil and corrosion resistance.
WS2 was coated on the surface of magnesium silicate (MSH) hydroxide by hydrothermal reaction method and carbonized to form an MSH@WS2-C nanocomposite material for the preparation of nanolubricating additives.
It significantly reduces the friction coefficient, improves lubricating performance and wear resistance, improves the dispersion stability and corrosion resistance in base oil, and makes the comprehensive performance of nanolubricating additives more stable and excellent.
Smart Images

Figure CN119685072A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nano-lubricating materials, and in particular relates to a MSH@WS2-C nano-lubricating additive, and also relates to a preparation method and application of the MSH@WS2-C nano-lubricating additive. Background Art
[0002] 23% of the world's total energy consumption is caused by contact friction. In the field of mechanical processing and metal parts application, the effect of lubricants is crucial. Lubricants with excellent drag reduction performance can greatly reduce unnecessary friction and wear consumption, improve machining and operation efficiency, and reduce the accident rate. Nanomaterials are widely used in the field of lubricants due to their large specific surface area and good adsorption. Due to the unique interlayer structure of the material, it has excellent lubrication performance and can greatly reduce the friction coefficient of lubricating oil. The emergence of various nanomaterials has promoted the development of the lubricant field. Nanomaterials of different forms and sizes can all play an excellent drag and wear reduction performance. WS2 is one of the representatives, and its lamellar structure can greatly improve the friction resistance of lubricants. MSH nanomaterials have excellent wear resistance and can form a complete and solid oxide friction film during friction. At the same time, various physical and chemical reactions occur as the friction proceeds. After being broken, they are filled in the wear defects of the friction disc such as grooves, furrows, corrosion pits, etc. to repair and fill the friction film. How to combine the excellent friction performance of WS2 with the excellent wear resistance of MSH to form a nanocomposite material with excellent comprehensive performance has become an urgent problem to be solved. The present invention provides a method for preparing a flower rod-shaped nano material of carbonized WS2 coated with MSH, which improves the friction performance of MSH and the wear reduction performance of WS2, combines materials of different dimensions, and effectively improves the lubrication performance of the nano lubricant.
[0003] Existing lubricant additives can achieve a low friction coefficient, but the wear resistance is weak, especially in the case of long-term friction and wear, the friction film is difficult to repair, and the longer the time, the worse the friction performance. Some other additives cannot take into account the time stability, dispersion stability in oil and corrosion resistance while having excellent friction and wear performance. After carbonization process treatment, not only can the friction performance of lubricant additives be improved, but the carbon layer on WS2 can also effectively improve the dispersion stability and corrosion resistance of additives in base oil, making the overall performance of additives more stable and excellent. Summary of the invention
[0004] The purpose of the present invention is to provide a MSH@WS2-C nano-lubricating additive, which solves the problem that the existing nano-lubricating additives have weak wear resistance.
[0005] The present invention also aims to provide a method for preparing the MSH@WS2-C nano-lubricating additive.
[0006] The present invention also aims to provide a lubricating oil containing the MSH@WS2-C nano-lubricating additive, which solves the problem of poor lubrication performance of nano-lubricants in the prior art.
[0007] The first technical solution adopted by the present invention is: MSH@WS2-C nano-lubricating additive, tungsten disulfide WS2 is coated on the surface of hydroxy magnesium silicate nanorods to form a rod-shaped MSH@WS2 nanomaterial coated on the surface of hydroxy magnesium silicate nanorods, and carbon is coated on the surface of the MSH@WS2 nanomaterial to form a MSH@WS2-C nano-composite material. The present invention is also characterized in that: Furthermore, the length of tungsten disulfide WS2 is 500-800nm, and lamellar sliding occurs with the relative movement of the friction pair during the friction process; the length of the magnesium hydroxysilicate nanorods is 300-600nm, and they enter the friction area during the friction process as micro-bearings, converting sliding friction into rolling friction.
[0008] The second technical solution adopted by the present invention is: a method for preparing MSH@WS2-C nano-lubricating additive, and the specific operation steps are as follows: Step 1: Magnesium chloride hexahydrate and sodium metasilicate nonahydrate are prepared into a solution, which is referred to as solution A. The pH is adjusted with sodium hydroxide, and a nano-scale MSH tube (magnesium hydroxide silicate Mg3Si2O5(OH)4, referred to as MSH) is obtained after a one-step hydrothermal reaction, and then MSH nanopowder is obtained after centrifugation, washing and drying; Step 2: The dried MSH powder, sodium tungstate dihydrate, thioacetamide and oxalic acid are mixed into a mixed solution, which is referred to as solution B, and a one-step hydrothermal reaction is performed to obtain MSH@WS2 nanomaterials coated with tungsten disulfide WS2; Step 3: After centrifuging, washing and drying the MSH@WS2 nanomaterial, MSH@WS2 nanopowder is obtained; Step 4: Evenly mix the MSH@WS2 nanopowder and glucose in deionized water, referred to as solution C, and perform a hydrothermal reaction to obtain carbonized MSH@WS2, i.e., MSH@WS2-C nanocomposite material; Step 5: After centrifuging, washing and drying the MSH@WS2-C nanocomposite material, the MSH@WS2-C nanolubricating additive is obtained.
[0009] The present invention is also characterized in that: The length of the MSH nanotube rods in step 1 is 300-600 nm; the reaction temperature of the one-step hydrothermal reaction is 200° C. and the reaction time is 24 h.
[0010] Step 1: Sodium hydroxide is used to adjust pH to 13.5.
[0011] The MSH concentration of solution B in step 2 is 4.45 mg / mL; 1.98 g of ammonium tungstate dihydrate, 1.8 g of thioacetamide, and 3 g of oxalic acid are added to every 180 mL of deionized water.
[0012] The hydrothermal reaction temperature in step 2 is 200°C and the reaction time is 24h.
[0013] The size of the MSH@WS2 nanomaterial in step 3 is: length 500-800nm, width 200nm.
[0014] In step 4, solution C is prepared by adding 1.5 g of MSH@WS2 and 0.25 g of glucose to every 180 mL of deionized water; the hydrothermal treatment is heated at 170° C. for 6 h.
[0015] The size of the MSH@WS2-C nanocomposite material in step 5 is 500-800 nm in length and 200 nm in width.
[0016] The third technical solution adopted by the present invention is the application of MSH@WS2-C nano-lubricating additive, mixing the MSH@WS2-C nano-lubricating additive with base oil to form lubricating oil; the mass proportion of the MSH@WS2-C nano-lubricating additive in the lubricating oil is 1.0wt%.
[0017] The base oil component comprises 5 to 15 parts of sodium carboxymethyl cellulose, 70 to 90 parts of polyurethane, 40 to 65 parts of emulsifier, 80 to 140 parts of polymethyl olefin alkali oil, 5 to 20 parts of anionic surfactant, 5 to 20 parts of nonionic surfactant and 10 to 100 parts of water.
[0018] The beneficial effects of the present invention are: In the present invention, WS2 is coated on the surface of magnesium silicate hydroxide (MSH) by a hydrothermal reaction method, followed by carbonization treatment. When 1.0wt% of MSH@WS2 is added to crude oil, the friction coefficient of the metal-to-metal friction pair is reduced from 0.2376 to 0.1235 under a load of 50N compared with crude oil, a decrease of 48%. After adding 1.0wt% of MSH@WS2-C, the friction coefficient is reduced from 0.2376 to 0.0736 under a load of 50N compared with crude oil, a decrease of 69%, and the lubrication effect of crude oil is greatly improved. The reason is that the carbonized composite material attaches carbon flakes on the surface of WS2, which is beneficial to improve the friction performance and protect WS2 from being oxidized temporarily. Wear marks of varying depths will be formed in the friction area of the metal-to-metal pair during the friction process. MSH can act as a micro-bearing in this process, converting sliding friction into rolling friction, and can fill in the wear marks to repair damage and wear defects on the surface of the metal-to-metal pair, thereby greatly improving the lubrication effect. WS2 is a lamellar material, which will undergo relative slip under the action of shear force, reducing friction resistance, and can be adsorbed on the surface of the friction pair to form a friction film. Various oxides generated by the physical and chemical reactions of MSH form a dense friction film, avoiding direct contact between the friction pairs during the friction process.
[0019] The preparation method of the present invention is simple, low-cost and has a short preparation cycle. After a mixed solution of magnesium chloride hexahydrate and sodium metasilicate nonahydrate is reacted by a one-pot hydrothermal method for 24 hours, nano-sized magnesium silicate hydroxide (MSH) is successfully prepared. The hollow tube rod-shaped MSH can be used as a micro-bearing in a friction pair to bear the lubrication and drag reduction effect. At the same time, MSH will undergo an oxidation reaction, and the generated oxides will be filled in the defects such as furrows and grooves generated by friction and wear to repair the friction film. At the same time, MSH can still stably play a lubricating role under long-term friction loads; since WS2 has excellent lubrication properties as a layered nanomaterial; carbonization can improve dispersion and friction properties. Therefore, the present invention selects sodium tungstate dihydrate and thioacetamide as tungsten sources and sulfur sources respectively, selects oxalic acid as a structure directing agent, reacts under hydrothermal conditions for 24 hours to synthesize rod-shaped WS2, and then carbonizes it, and synergistically improves the performance of the lubricating additive with the hollow tube rod-shaped MSH. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1(a) is a TEM image of MSH prepared in Example 2.
[0021] Figure 1(b) is a TEM image of WS2 prepared in Example 2.
[0022] Figure 2 This is the TEM image of sample MSH@WS2 in Example 2.
[0023] Figure 3 This is the TEM image of sample MSH@WS2-C in Example 2.
[0024] Figure 4 This is the friction coefficient curve of the sample in Example 2 (friction 0.5h).
[0025] Figure 5 is the average friction coefficient of the samples in Example 2.
[0026] Figure 6 is the average friction coefficient of the samples in Example 2 (friction for 1 h). DETAILED DESCRIPTION
[0027] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments so that the advantages and features of the present invention can be more easily understood by those skilled in the art.
[0028] The preparation method of the MSH@WS2 nano-lubricating additive of the present invention comprises the following steps: 1) Take magnesium chloride hexahydrate and sodium metasilicate nonahydrate as raw materials, dissolve them in deionized water and stir them evenly, titrate them with sodium hydroxide solution to pH=13.5, transfer the solution to a reactor for heating reaction at 200°C for 24 hours, collect the product after the reaction, filter it, wash it with deionized water and anhydrous ethanol for 3 to 5 times, dry it in an oven at 60 to 80°C, and obtain nanotubular MSH powder after drying; 2) Weigh the dried MSH powder and dissolve it in deionized water, stir it evenly at room temperature, add ammonium tungstate dihydrate and thioacetamide, and continue stirring for 1 hour after forming a mixed solution. Then add oxalic acid and continue stirring for 30 minutes. The molar concentration ratio of sodium tungstate dihydrate and thioacetamide is 1:4, and the concentrations are 0.011g / mL and 0.01g / mL respectively; the concentration of oxalic acid is 0.167g / mL, and the mass of MSH powder is 0.8g; 3) The mixed solution prepared in step 2) was transferred to a polytetrafluoroethylene-lined reactor and heated for hydrothermal reaction at 200°C for 24 hours. After the reaction, the product was washed with deionized water and anhydrous ethanol for 3 to 5 times, and dried in an oven at 60 to 80 times for 24 hours to obtain MSH@WS2 nanopowder.
[0029] 4) Weigh the dried MSH@WS2 nanopowder and dissolve it in deionized water, add glucose, and stir at room temperature for 30 min to mix evenly. The concentrations of MSH@WS2 and glucose are 0.0084 g / mL and 0.0014 g / mL, respectively; 5) The mixed solution prepared in step 4) was transferred to a polytetrafluoroethylene-lined reactor and heated for hydrothermal reaction at 170°C for 6 hours. After the reaction, the product was washed with deionized water and anhydrous ethanol for 3 to 5 times, and dried in an oven at 60 to 80 times for 24 hours to obtain the MSH@WS2-C nano-lubricating additive.
[0030] Example 1 1) Take magnesium chloride hexahydrate and sodium metasilicate nonahydrate as raw materials, dissolve them in 180mL deionized water and stir evenly, the concentrations of the two are 0.055g / mL and 0.051g / mL respectively, titrate with sodium hydroxide solution to pH=13.5, transfer the solution to a reactor for heating reaction at 200°C for 24h, collect the product after the reaction, filter it, wash it with deionized water and anhydrous ethanol for 5 times, dry it in an oven at 70°C for 12h, and obtain nanotubular MSH powder after drying; 2) Weigh the dried MSH powder and dissolve it in 180 mL of deionized water, stir evenly at room temperature, add ammonium tungstate dihydrate and thioacetamide, and continue stirring for 1 hour after forming a mixed solution. Subsequently, add oxalic acid and continue stirring for 30 minutes, wherein the molar concentration ratio of sodium tungstate dihydrate and thioacetamide is 1:4, and the concentrations are 0.011 g / mL and 0.01 g / mL, respectively; the mass of MSH powder is 0.8 g, and the concentration is 4.45 mg / mL; the mass of oxalic acid is 1.5 g, and the concentration is 0.0084 g / mL; 3) The mixed solution prepared in step 2) was transferred to a polytetrafluoroethylene-lined reactor and heated for hydrothermal reaction at 200°C for 24 h. After the reaction, the product was washed 5 times with deionized water and anhydrous ethanol, and dried in an oven at 70°C for 12 h to obtain MSH@WS2 nanopowder.
[0031] 4) Weigh the dried MSH@WS2 nanopowder and dissolve it in deionized water, add glucose, and stir for 30 min at room temperature to mix evenly. The concentrations of MSH@WS2 nanopowder and glucose are 0.0084 g / mL and 0.0014 g / mL, respectively; 5) The mixed solution prepared in step 4) was transferred to a polytetrafluoroethylene-lined reactor and heated for hydrothermal reaction at 170°C for 6 hours. After the reaction, the product was washed with deionized water and anhydrous ethanol for 3 to 5 times, and dried in an oven at 60 to 80 times for 24 hours to obtain the MSH@WS2-C nano-lubricating additive.
[0032] Example 2 1) Magnesium chloride hexahydrate and sodium metasilicate nonahydrate were used as raw materials, dissolved in 180 mL of deionized water and stirred evenly. The concentrations of the two were 0.055 g / mL and 0.051 g / mL, respectively. The solution was titrated with sodium hydroxide solution to pH = 13.5. The solution was transferred to a reactor for heating reaction at 200 ° C for 24 h. After the reaction was completed, the product was collected, filtered, washed with deionized water and anhydrous ethanol for 5 times, and dried in an oven at 70 ° C for 12 h. After drying, nano-tubular MSH powder was obtained. The structure of MSH is shown in Figure 1, showing a hollow tube rod shape; 2) Weigh the dried MSH powder and dissolve it in 180 mL of deionized water, stir evenly at room temperature, add ammonium tungstate dihydrate and thioacetamide, and continue stirring for 1 hour after forming a mixed solution. Subsequently, add oxalic acid and continue stirring for 30 minutes, wherein the molar concentration ratio of sodium tungstate dihydrate and thioacetamide is 1:4, and the concentrations are 0.011 g / mL and 0.0102 g / mL respectively; the mass of MSH powder is 0.8 g, and the concentration is 4.45 mg / mL; the mass of oxalic acid is 3 g, and the concentration is 0.0167 g / mL; 3) The mixed solution prepared in step 2) was transferred to a polytetrafluoroethylene-lined reactor and heated for hydrothermal reaction at 200°C for 24 h. After the reaction, the product was washed 5 times with deionized water and anhydrous ethanol, and dried in an oven at 70°C for 12 h to obtain MSH@WS2 nanopowder.
[0033] 4) Weigh the dried MSH@WS2 nanopowder and dissolve it in deionized water, add glucose, and stir for 30 min at room temperature to mix evenly. The concentrations of MSH@WS2 nanopowder and glucose are 0.0084 g / mL and 0.0014 g / mL, respectively; 5) The mixed solution prepared in step 4) was transferred to a polytetrafluoroethylene-lined reactor and heated for hydrothermal reaction at 170°C for 6 hours. After the reaction, the product was washed with deionized water and anhydrous ethanol for 3 to 5 times, and dried in an oven at 60 to 80 times for 24 hours to obtain the MSH@WS2-C nano-lubricating additive.
[0034] Example 3 1) Take magnesium chloride hexahydrate and sodium metasilicate nonahydrate as raw materials, dissolve them in 180mL deionized water and stir evenly, the concentration of both is 0.0108g / mL, titrate with sodium hydroxide solution to pH=13.5, transfer the solution to a reactor for heating reaction at 200°C for 24h, collect the product after the reaction, filter it, wash it with deionized water and anhydrous ethanol 5 times, dry it in an oven at 70°C for 12h, and obtain nanotubular MSH powder after drying; 2) Weigh the dried MSH and dissolve it in 180 mL of deionized water, stir evenly at room temperature, add ammonium tungstate dihydrate and thioacetamide, and continue stirring for 1 hour after forming a mixed solution. Subsequently, add oxalic acid and continue stirring for 30 minutes, wherein the molar concentration ratio of sodium tungstate dihydrate and thioacetamide is 1:4, and the concentrations are 0.011 g / mL and 0.01 g / mL respectively; the mass of MSH is 0.8 g, and the concentration is 4.45 mg / mL; the mass of oxalic acid is 4.5 g, and the concentration is 0.025 g / mL; 3) The mixed solution prepared in step 2) was transferred to a polytetrafluoroethylene-lined reactor and heated for hydrothermal reaction at 200°C for 24 h. After the reaction, the product was washed 5 times with deionized water and anhydrous ethanol, and dried in an oven at 70°C for 12 h to obtain MSH@WS2 nanopowder.
[0035] 4) Weigh the dried MSH@WS2 and dissolve it in deionized water, add glucose, and stir at room temperature for 30 min to mix evenly. The concentrations of MSH@WS2 and glucose are 0.0084 g / mL and 0.0014 g / mL, respectively; 5) The mixed solution prepared in step 4) was transferred to a polytetrafluoroethylene-lined reactor and heated for hydrothermal reaction at 170°C for 6 hours. After the reaction, the product was washed with deionized water and anhydrous ethanol for 3 to 5 times, and dried in an oven at 60 to 80 times for 24 hours to obtain the MSH@WS2-C nano-lubricating additive.
[0036] As shown in Figure 1 (a), a hollow tube-shaped MSH was prepared, and as shown in Figure 1 (b), a rod-shaped WS2 was prepared; Figure 2 This is the TEM image of sample MSH@WS2 of Example 2; the prepared MSH@WS2 composite material is in the shape of a flower stick, with the two substances inside and outside evenly distributed, and the flower-shaped WS2 is evenly coated on MSH.
[0037] Figure 3 This is the TEM image of sample MSH@WS2-C in Example 2; the prepared MSH@WS2-C composite material is in the shape of a rod flower, and the carbon element is evenly distributed on the surface of MSH@WS2.
[0038] Figure 4This is the friction coefficient curve of the sample in Example 2 (friction 0.5h); it can be seen that the base oil without additives has a higher friction coefficient and poorer friction resistance, while the friction coefficient of the lubricating oil is greatly reduced after adding the two composite materials, among which the friction coefficient of sample MSH@WS2-C is significantly lower than that of sample MSH@WS2, which indicates that the carbonized sample has better friction performance.
[0039] Figure 5 is the average friction coefficient of the samples in Example 2; the average friction coefficient of the base oil without additives is about 0.23, after adding 1.0wt% of MSH@WS2, the average friction coefficient is reduced to about 0.13, and after adding 1.0wt% of MSH@WS2-C, the average friction coefficient is reduced to about 0.07, showing the excellent lubrication performance of the additive of the present invention, and the carbonized nanocomposite material exhibits more excellent friction performance.
[0040] Figure 6 This is the friction coefficient curve (friction 1h) of the lubricating oil to which 1.0wt% of the MSH@WS2-C sample is added in Example 2. As the friction test time increases, after 32min, the friction coefficient gradually decreases with time, which reflects the excellent wear resistance of MSH in repairing the friction film and filling the wear pits.
[0041] Example 4 The MSH@WS2-C nano-lubricating additive of the present invention coats tungsten disulfide WS2 on the surface of magnesium hydroxysilicate nanorods to form a rod-flower-shaped MSH@WS2 nano-material coated on the surface of magnesium hydroxysilicate nano-rods, and coats carbon on the surface of the MSH@WS2 nano-material to form a MSH@WS2-C nano-composite material.
[0042] Example 5 The application of MSH@WS2-C nano-lubricating additive is to mix the MSH@WS2-C nano-lubricating additive with base oil to form lubricating oil; the mass proportion of the MSH@WS2-C nano-lubricating additive in the lubricating oil is 1.0wt%.
[0043] The base oil component comprises 5 to 15 parts of sodium carboxymethyl cellulose, 70 to 90 parts of polyurethane, 40 to 65 parts of emulsifier, 80 to 140 parts of polymethyl olefin alkali oil, 5 to 20 parts of anionic surfactant, 5 to 20 parts of nonionic surfactant and 10 to 100 parts of water.
[0044] Example 6 The preparation method of the MSH@WS2-C nano-lubricating additive of the present invention has the following specific steps: Step 1: Magnesium chloride hexahydrate and sodium metasilicate nonahydrate are prepared into a solution, which is referred to as solution A. The pH value is adjusted with sodium hydroxide. A nanoscale MSH tube is obtained after a one-step hydrothermal reaction, and then MSH nanopowder is obtained after centrifugation, washing and drying. Step 2: The dried MSH powder, sodium tungstate dihydrate, thioacetamide and oxalic acid are prepared into a mixed solution, which is recorded as solution B, and a one-step hydrothermal reaction is performed to obtain MSH@WS2 nanomaterials coated with tungsten disulfide WS2; Step 3: After centrifuging, washing and drying the MSH@WS2 nanomaterial, MSH@WS2 nanopowder is obtained; Step 4: Evenly mix the MSH@WS2 nanopowder and glucose in deionized water, referred to as solution C, and perform a hydrothermal reaction to obtain carbonized MSH@WS2, i.e., MSH@WS2-C nanocomposite material; Step 5: After centrifuging, washing and drying the MSH@WS2-C nanocomposite material, the MSH@WS2-C nanolubricating additive is obtained.
[0045] Example 7 Based on Example 6, The length of the MSH nanotube rods in step 1 is 300-600 nm; the reaction temperature of the one-step hydrothermal reaction is 200° C. and the reaction time is 24 h.
[0046] The MSH concentration of solution B in step 2 is 4.45 mg / mL; 1.98 g of ammonium tungstate dihydrate, 1.8 g of thioacetamide, and 3 g of oxalic acid are added to every 180 mL of deionized water.
[0047] Step 2: The hydrothermal reaction temperature is 200°C and the reaction time is 24 h. The size of the MSH@WS2 nanomaterial in step 3 is: length 500-800nm, width 200nm.
[0048] Solution C in step 4 is prepared by adding 1.5 g of MSH@WS2 and 0.25 g of glucose to every 180 mL of deionized water; the hydrothermal treatment is heated at 170° C. for 6 h.
[0049] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. MSH@WS2-C nano lubricant additive, characterized in that: Tungsten disulfide WS2 is coated on the surface of magnesium silicate hydroxy nanorods to form a rod-flower-shaped MSH@WS2 nanomaterial coated on the surface of magnesium silicate hydroxy nanorods, and carbon is coated on the surface of the MSH@WS2 nanomaterial to form a MSH@WS2-C nanocomposite material.
2. The MSH@WS2-C nano-lubricating additive according to claim 1, characterized in that: The tungsten disulfide WS2 has a length of 500-800 nm, and produces lamellar sliding as the friction pair moves relative to each other during the friction process; the hydroxy magnesium silicate nanorods have a length of 300-600 nm, and enter the friction area during the friction process as micro-bearings, converting sliding friction into rolling friction.
3. The preparation method of MSH@WS2-C nano-lubricating additive is characterized in that: The specific steps are as follows: Step 1: Magnesium chloride hexahydrate and sodium metasilicate nonahydrate are prepared into a solution, which is referred to as solution A. The pH value is adjusted with sodium hydroxide. A nanoscale MSH tube is obtained after a one-step hydrothermal reaction, and then MSH nanopowder is obtained after centrifugation, washing and drying. Step 2: The dried MSH powder, sodium tungstate dihydrate, thioacetamide and oxalic acid are prepared into a mixed solution, which is recorded as solution B, and a one-step hydrothermal reaction is performed to obtain MSH@WS2 nanomaterials coated with tungsten disulfide WS2; Step 3: After centrifuging, washing and drying the MSH@WS2 nanomaterial, MSH@WS2 nanopowder is obtained; Step 4: Evenly mix the MSH@WS2 nanopowder and glucose in deionized water, referred to as solution C, and perform a hydrothermal reaction to obtain carbonized MSH@WS2, i.e., MSH@WS2-C nanocomposite material; Step 5: After centrifuging, washing and drying the MSH@WS2-C nanocomposite material, the MSH@WS2-C nanolubricating additive is obtained.
4. The method for preparing the MSH@WS2-C nano-lubricating additive according to claim 3, characterized in that: The length of the MSH nanotube rod in step 1 is 300-600 nm; the reaction temperature of the one-step hydrothermal reaction is 200° C. and the reaction time is 24 h; sodium hydroxide is used to adjust the pH to 13.
5.
5. The method for preparing the MSH@WS2-C nano-lubricating additive according to claim 3, characterized in that: The MSH concentration of solution B in step 2 is 4.45 mg / mL; 1.98 g of ammonium tungstate dihydrate, 1.8 g of thioacetamide, and 3 g of oxalic acid are added to every 180 mL of deionized water.
6. The method for preparing the MSH@WS2 nano-lubricating additive according to claim 3, characterized in that: The hydrothermal reaction temperature in step 2 is 200°C and the reaction time is 24h.
7. The method for preparing the MSH@WS2-C nano-lubricating additive according to claim 3, characterized in that: The size of the MSH@WS2 nanomaterial in step 3 is: length 500-800nm, width 200nm.
8. The method for preparing the MSH@WS2-C nano-lubricating additive according to claim 3, characterized in that: In step 4, solution C is prepared by adding 1.5 g of MSH@WS2 and 0.25 g of glucose to every 180 mL of deionized water; the hydrothermal treatment is heated at 170° C. for 6 h.
9. The method for preparing the MSH@WS2-C nano-lubricating additive according to claim 3, characterized in that: The size of the MSH@WS2-C nanocomposite material in step 5 is 500-800 nm in length and 200 nm in width.
10. Application of MSH@WS2-C nano-lubricating additive, characterized in that: The MSH@WS2-C nano-lubricating additive is mixed with the base oil to form a lubricating oil; the mass proportion of the MSH@WS2-C nano-lubricating additive in the lubricating oil is 1.0wt%; The base oil component comprises 5 to 15 parts of sodium carboxymethyl cellulose, 70 to 90 parts of polyurethane, 40 to 65 parts of emulsifier, 80 to 140 parts of polymethyl olefin alkali oil, 5 to 20 parts of anionic surfactant, 5 to 20 parts of nonionic surfactant and 10 to 100 parts of water.